2018
DOI: 10.1007/s00404-018-4779-4
|View full text |Cite|
|
Sign up to set email alerts
|

Breast cancer patients’ satisfaction with individual therapy goals and treatment in a standardized integrative medicine consultancy service

Abstract: Using a standardized procedure in integrative medicine allows a high quality level to be offered to patients. Overall, breast cancer patients report very high satisfaction with the integrative medicine consultancy service and state long-term treatment goals. Hence, long-term treatment with integrative medicine methods should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 20 publications
2
35
1
Order By: Relevance
“…Interestingly enough, only 27% of our study population expressed the wish for implementation of psychological counseling into cancer care, whereas 54% did so with respect to CAM concepts and 43% to dietary counseling. Hack et al [56 ]were aware of breast cancer patients' growing interest in integrative therapeutic approaches but came to realize that published data on how to implement a comprehensive consultancy service on integrative medicine were missing. Hence, they developed a standardized procedure for conducting an integrative medicine consultation and incorporating it into routine patient care at the Department of OBGYN in Erlangen, Germany.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly enough, only 27% of our study population expressed the wish for implementation of psychological counseling into cancer care, whereas 54% did so with respect to CAM concepts and 43% to dietary counseling. Hack et al [56 ]were aware of breast cancer patients' growing interest in integrative therapeutic approaches but came to realize that published data on how to implement a comprehensive consultancy service on integrative medicine were missing. Hence, they developed a standardized procedure for conducting an integrative medicine consultation and incorporating it into routine patient care at the Department of OBGYN in Erlangen, Germany.…”
Section: Discussionmentioning
confidence: 99%
“…A careful history of the woman's use of herbs, supplements, and alternative medications must be taken. Referral to an expert in complementary medicine should be done if a woman chooses to pursue these options . See Appendix for complementary and alternative medicine resources.…”
Section: Long‐term Care Of the Breast Cancer Survivormentioning
confidence: 99%
“…Incorporation of multivitamins that support bone and cardiac health, as well as vitamin D supplements, are recommended . Bone loss is greater than normal for age in women after breast cancer treatment, so calcium 1200 mg and vitamin D 1000 mg daily are recommended for all women past age 50 . One study also found an association between vitamin D supplements and a decreased risk of cancer recurrence in women with estrogen receptor‐positive breast cancer …”
Section: Long‐term Care Of the Breast Cancer Survivormentioning
confidence: 99%
See 2 more Smart Citations